2017
DOI: 10.18632/oncotarget.19355
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between protein kinase catalytic subunit alpha-1 gene rs13361707 polymorphism and gastric cancer susceptibility in asian populations

Abstract: A single nucleotide polymorphism (SNP) of the protein kinase catalytic subunit alpha-1 gene (PRKAA1) that confers susceptibility to gastric cancer (GC) was identified by genome-wide association in several case-control studies. However, the results remained controversial and ambiguous. Therefore, we performed a larger meta-analysis to confirm this association. We searched the PubMed, Embase, WanFang, and CNKI databases, without any restriction on language, covering all papers published until Feb 22, 2017. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…20 However, a recent meta-analysis combining all included studies showed no relationship between this SNP and GC risk in Asians. 21 breast cancer risk. 22 Another study implied rs13361707 C/T polymorphism was unrelated to lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, a recent meta-analysis combining all included studies showed no relationship between this SNP and GC risk in Asians. 21 breast cancer risk. 22 Another study implied rs13361707 C/T polymorphism was unrelated to lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Europe with mixed Caucasian populations obtained negative results for the association between this SNP and GC risk 20 . However, a recent meta‐analysis combining all included studies showed no relationship between this SNP and GC risk in Asians 21 . A study of 1340 breast cancer cases and 2536 controls in Caucasians obtained no association between this polymorphism and breast cancer risk 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have been recognized as an effective method to summarize and review previously published quantitative research to answer a wide variety of clinical questions [55]. However, several limitations in our meta-analysis should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed an association between TLR1 rs4833095 and GC, but we did not find the association of this SNP with a susceptibility to H. pylori infection or presence of AG. PRKAA1 rs13361707 has been evaluated in several GC genetic association studies [16,21,[24][25][26][27][42][43][44][45][46][47], following identification of this SNP as a risk factor for non-cardia GC in GWAS in 2011 [22]. The systematic review and meta-analysis by Mocellin et al (2015) supported the link between PRKAA1 rs13361707 and an increased risk of noncardia subtype GC [46].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, one study found that PRKAA1 polymorphisms may have an influence to H. pylori infection development and a synergetic effect on the risk of development of GC [26]. However, the direction of this association remains ambiguous and the polymorphism may even be inversely related to GC risk [27].…”
Section: Introductionmentioning
confidence: 99%